Perbedaan Antara Sistem Keuangan Islam Dan Konvensional - Enceng Iip Syaripudin; Deni Konkon Furkony (STIES INDONESIA PURWAKARTA Dan MES PURWAKARTA, 2020)
The financial system of a country is greatly influenced by the economic system it adopts. The economic system refers to a single set of decision-making mechanisms and institutions that implement these decisions on production, consumption and income distribution. Therefore, the economic system is something that is important for the economy of a country. The Islamic Financial System is the basis of economic strength in this country, in its day it was able to become a system that could prosper its people. In times of crisis, he was able to escape bankruptcy, even though he did not receive assistance or disbursement of BLBI funds. This Islamic concept should be a new force in reviving the country's economy. The Islamic Financial System is developing rapidly to play its role in allocating resources and enhancing economic development. The objectives to be achieved in this study are: 1) What distinguishes the Islamic financial system and conventional financial systems. 2). To find out the strengths and weaknesses between the Islamic and conventional financial systems. The research method used in this research is the library research method or book survey. The library research method is a research method in which data collection techniques are carried out in the field (library) based on the readings of several literatures that have information and are relevant to the research topic. Based on the results of the study, it is concluded that the advantages of Islamic finance can survive various economic crises that are faced, this is evidenced by the increase and development of Indonesian Islamic Banking compared to conventional banks.